2007
DOI: 10.1051/0004-6361:20077899
|View full text |Cite
|
Sign up to set email alerts
|

Results from Droxo

Abstract: Aims. We study the variability of the Fe 6.4 keV emission line from the Class I young stellar object Elias 29 in the ρ Oph cloud. Methods. We analysed the data from Elias 29 collected by XMM-Newton during a nine-day, nearly continuous observation of the ρ Oph star-forming region (the Deep Rho-Oph X-ray Observation, named droxo). The data were subdivided into six homogeneous time intervals, and the six resulting spectra were individually analysed. Results. We detect significant variability in the equivalent wid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
40
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 26 publications
11
40
1
Order By: Relevance
“…A meaningful sample of CTTS fluorescent signatures is available , with several unexpected features deserving further study. Specifically, strong fluorescence in the Class I protostar Elias 29 (in the ρ Oph region) appears to be quasi-steady rather than related to strong X-ray flares (Favata et al 2005); even more perplexing, the 6.4 keV line is modulated on time scales of days regardless of the nearly constant stellar X-ray emission; it also does not react to the occurrence of appreciable X-ray flares in the light curve (Giardino et al 2007). The latter authors suggested that here we see 6.4 keV emission due to non-thermal electron impact in relatively dense, accreting magnetic loops.…”
Section: X-ray Fluorescencementioning
confidence: 99%
“…A meaningful sample of CTTS fluorescent signatures is available , with several unexpected features deserving further study. Specifically, strong fluorescence in the Class I protostar Elias 29 (in the ρ Oph region) appears to be quasi-steady rather than related to strong X-ray flares (Favata et al 2005); even more perplexing, the 6.4 keV line is modulated on time scales of days regardless of the nearly constant stellar X-ray emission; it also does not react to the occurrence of appreciable X-ray flares in the light curve (Giardino et al 2007). The latter authors suggested that here we see 6.4 keV emission due to non-thermal electron impact in relatively dense, accreting magnetic loops.…”
Section: X-ray Fluorescencementioning
confidence: 99%
“…4 we compare these values against the evidences of an older stellar age. For a star in A128, page 2 of 12 the 0.5-2 Gyr age time interval, corresponding to an age between that of the Hyades and of stars in NGC 752 open cluster, the X-ray luminosity of late F stars should be approximately in the range 28.1 < log L X < 29.5 (Pallavicini et al 1981;Stern et al 1995;Randich & Schmitt 1995;Giardino et al 2007). …”
Section: Age Of Wasp-18mentioning
confidence: 99%
“…In X-rays, several Chandra observations have targeted L1688 for a total duration of about 400 ks (Imanishi et al 2001;Gagné et al 2004). XMM-Newton has also observed L1688 with a 35 ks exposure (Ozawa et al 2005), and with a large program named DROXO (PI: S. Sciortino, exposure ∼500 ks) aimed at obtaining a deep observation to characterize the X-rays properties of the YSOs embedded in the L1688 core (Giardino et al 2007;Flaccomio et al 2009;Pillitteri et al 2010). X-ray surveys have demonstrated the frequent variability of YSOs in L1688 (see Montmerle et al 1983), and the first cases of detected neutral Fe line at 6.4 keV in stellar X-ray spectra, due to the interaction of high energy photons from the central object and cold material in the circumstellar disk.…”
Section: Introductionmentioning
confidence: 99%